Strategy for Strengthening the Implementation of Progressive Law in the Republic of Indonesia National Police - Muchtarom, Achmad; Barthos, Megawati (Ridwan Institute, 2025)
Law enforcement in Indonesia today faces serious challenges, especially in maintaining a balance between procedural justice and substantive justice. The Indonesian National Police as one of the law enforcement institutions has a strategic role in realizing a legal system that is not only based on normative legality, but also upholds the values of humanity, morality, and social justice. In this context, the progressive legal approach introduced by Satjipto Rahardjo is very relevant to be adopted and implemented by the Indonesian National Police. Progressive law offers a new paradigm in law enforcement that sides with the people, rejects procedural rigidity, and prioritizes humanitarian values as the substance of law. This study aims to normatively examine the concept of progressive law about the role and function of the Indonesian National Police and to formulate strategies that can be used to strengthen the implementation of the progressive legal approach within the Indonesian National Police. This study uses a normative juridical method, with a statutory regulatory approach and a conceptual approach. The legal materials used consist of primary legal materials such as the 1945 Constitution of the Republic of Indonesia, Law Number 2 of 2002 concerning the Indonesian National Police, and other related regulations. In addition, secondary legal materials are also used in the form of legal literature, scientific journals, and the views of legal experts on progressive law. This study is expected to provide theoretical contributions to the development of progressive legal discourse and provide a conceptual basis for institutional renewal within the National Police to create just and humanistic law enforcement.